2004
DOI: 10.1590/s1413-78522004000400001
|View full text |Cite
|
Sign up to set email alerts
|

Análise clínica e biomecânica do efeito do diclofenaco sódico na consolidação da fratura da tíbia no rato

Abstract: Os AINH (Antiinflamatórios não hormonais) são agentes utilizados na prática clínica que interferem no processo inflamatório pela inibição da síntese de prostaglandinas e tromboxanos. Alguns trabalhos experimentais investigaram sua ação no processo de consolidação de fraturas, por meio de estudos clínicos e histológicos, sendo escassas as análises biomecânicas. Nesse estudo foram utilizados 20 ratos da linhagem Wistar, divididos aleatoriamente em dois grupos iguais: grupo A (controle) e grupo B (tratado com dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The healing potential of a bone fracture depends on patient-related variables, location and the treatment employed. These variables must create biological and mechanical conditions that favor the repair process by influencing factors that are determinant for the organization and final process of fracture consolidation (Muller et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The healing potential of a bone fracture depends on patient-related variables, location and the treatment employed. These variables must create biological and mechanical conditions that favor the repair process by influencing factors that are determinant for the organization and final process of fracture consolidation (Muller et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These observations were in agreement with previous reports. Diclofenac-therapy may induce gastrointestinal disorders during the first days of administration (Muller et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This diclofenac dose was selected since it is widely used to inhibit cyclooxygenase, thus decreasing the synthesis of inflammatory mediators. Previous research in our laboratory demonstrated that rats given intramuscularly this dose had no ulceration (Muller et al, 2004). Therapeutically diclofenac dose ranges from 2 to 10 mg/kg per day, and it can be given intramuscularly, intraperitoneally and subcutaneously (Muller et al, 2004).…”
Section: Animals and Experimental Proceduresmentioning
confidence: 97%
See 1 more Smart Citation
“…Contudo, em ensaios piloto realizados, observou-se a fratura óssea ocorria no ponto de contato do osso com o atuador, distante da falha óssea, ilustrando que a maior concentração de carga não estava ocorrendo no local da falha. Por esse motivo, optou-se pela realização do ensaio de flexão em três pontos com o atuador aplicando a carga diretamente sobre a região da falha, como descrito por Müller et al (2004), e após novo ensaio piloto, notou-se que a fratura ocorria no local da falha.…”
Section: Ensaio Biomecânicounclassified